Evaluating the Use of Critical Current Density Tests of Symmetric Lithium Transference Cells with Solid Electrolytes - Fuchs, Till; Haslam, Catherine G.; Richter, Felix H.; Sakamoto, Jeff; Janek, Jürgen; Justus Liebig University Giessen (My University, 2023)
Alkali metal filament penetration into solid electrolytes causes short circuit induced cell failure, commonly evaluated using the bidirectional critical current density (CCD) test with stepwise increases in current density in alternating directions across symmetric lithium cells. However, the CCD is neither intrinsic to the cell nor to the material but rather depends on various extrinsic factors, such as current profile, transferred charge, pressure, resting intervals, and interface chemistry. The purpose of this study is to disambiguate the interpretation of CCD analyses in the literature and propose alternative approaches to analyze the stability and kinetics of the alkali metal/solid electrolyte interface. Two types of failure modes of electrochemical cells with solid electrolytes are defined: 1) failure of the solid electrolyte by crack formation coupled with or followed by dendrite growth, and 2) failure of the alkali metal electrode by the formation of pores at the interface with the solid electrolyte followed by filament initiation that eventually leads to short-circuiting. Therefore, the study recommends that CCD tests specify the failure mode. It is demonstrated that unidirectional polarization enablesunambiguous differentiation between failure modes. The proposals for bi- and unidirectional testing presented here are expected to provide more reliable and consistent CCD values across the community.
Keywords: ddc:540